2007
DOI: 10.1007/s00262-006-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of human PC-346C prostate cancer growth in mice by a xenogeneic tissue vaccine

Abstract: Vaccination, as an approach to prostate cancer, has largely focused on immunotherapy utilizing specific molecules or allogeneic cells. Such methods are limited by the focused antigenic menu presented to the immune system and by immunotolerance to antigens recognized as "self". To examine if a xenogeneic tissue vaccine could stimulate protective immunity in a human prostate cancer cell line, a vaccine was produced by glutaraldehyde fixation of harvested PAIII prostate cancer cells tumors (GFT cell vaccine) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This may explain a previous report by Suckow, et al . that showed that prostate tissue vaccine stimulated a Th1 response and specifically prevented prostate cancer growth [19], [44]. In a future study, it will be of interest to assess the effects of SIS, with or without non-self antigens, on expressions of co-stimulatory molecules by antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain a previous report by Suckow, et al . that showed that prostate tissue vaccine stimulated a Th1 response and specifically prevented prostate cancer growth [19], [44]. In a future study, it will be of interest to assess the effects of SIS, with or without non-self antigens, on expressions of co-stimulatory molecules by antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further, tumor material harvested from other sources could be used for preparation of vaccines. For example, our laboratory has previously shown that a xenogeneic tissue vaccine composed of harvested subcutaneous PAIII prostate tumors in LW rats stimulated sufficient immunity in immunocompetent Ncr-Foxn1 \nu[ mice such that, when their splenocytes were incubated with human PC346C prostate cancer cells and administered to syngeneic nu/nu mice, nearly 70% of the immunodeficient mice were completely free of tumor growth compared to none of the controls [17]. It appeared that this protective response was mediated by Th1 immunity.…”
Section: Discussionmentioning
confidence: 99%
“…185 Another approach using a xenogeneic tissue vaccine has recently been shown to stimulate protective immunity against human PC cells. 186 …”
Section: Whole-tumour Cell Vaccinesmentioning
confidence: 99%